Africa Agriculture Transformation Scorecard: performance and lessons. Lesotho - Khesa, M.; Greffiths, Ikhothatseng Jacob; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso; Fakudze, Bhekiwe (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2021)
This brief highlights Lesotho’s performance in the second BR and assesses challenges faced and lessons learned by Lesotho during the review. The brief also reviews policy and programmatic changes in Lesotho that can be attributed to the first (2017) and second BRs. It concludes by highlighting required policy actions for Lesotho to implement to meet the Malabo commitments by 2025.